Strain Specific Responses in a Microbead Rat Model of Experimental Glaucoma. (4th March 2021) - Eastlake, Karen; Jayaram, Hari; Luis, Joshua; Hayes, Matthew; Khaw, Peng T.; Limb, G. Astrid
ABSTRACT: Purpose: A major challenge in glaucoma research is the lack of reproducible animal models of RGC and optic nerve damage, the characteristic features of this condition. We therefore examined the glaucomatous responses of two different rat strains, the Brown Norway (BN) and Lister Hooded (LH) rats, to high intraocular pressure (IOP) induced by injection of magnetic beads into the anterior chamber. Methods: Magnetic microsphere suspensions (20 µl of 5–20 mg/ml) were injected into the anterior chamber of BN (n = 9) or LH (N = 15) rats. Animals from each strain were divided into three groups, each receiving a different dose of microspheres. IOP was measured over 4 weeks using a rebound tonometer. Retinal ganglion cell (RGC) damage and function were assessed using scotopic electroretinograms (ERGs), retinal flatmounts and optic nerve histology. ANOVA and Student's t -tests were used to analyse the data. Results: A significant elevation in IOP was observed in BN rats receiving injections of 20 mg (37.18 ± 12.28 mmHg) or 10 mg microspheres/ml (36.95 ± 13.63 mmHg) when compared with controls (19.63 ± 4.29 mmHg) ( p < .001) over 2 weeks. This correlated with a significant impairment of RGC function, as determined by scotopic ERG ( p < .001), reduction in axon number ( p < .05) and lower RGC density ( P < .05) in animals receiving 20 mg or 10 mg microspheres/ml as compared with controls. LH rats receiving similar microsphere doses showed reduced scotopic ERG function ( p < .001) after 2 weeks. No changes in IOP was seen in this strain, although a reduction in axon density was observed in optic nerve cross-sections ( p < .05). Initial changes in IOP and ERG responses observed in BN rats remained unchanged for a duration of 7 weeks. In LH animals, ERG responses were decreased at 1–2 weeks and returned to control levels after 5 weeks. Conclusions: Although this model was easily reproducible in BN rats, the phenotype of injury observed in LH rats was very different from that observed in BN animals. We suggest that differences in the glaucomatous response observed in these two strains may be ascribed to anatomical and physiological differences and merits further investigation.